EL 48 INTERPRETADO POR LA NIÑEZ DE LA ÉPOCA - Muñoz Guillén, Mercedes (2023)
It purports to show changes in every day life, as perceived by children of that time, as a result of 1948 armed conflict and its social impact in the decades following. From the theoretical point of view, the analysis of these narratives allows you to understand that memory is a collective construction, a dynamic which is not neutral because it is linked to social and cultural values and present needs.